Surveillance of carbapenem-resistant Klebsiella pneumoniae in a paediatric hospital in China revealed the dynamics of carbapenemase and the prevalence of ST2735 K. pneumoniae. Issue 1 (21st January 2022) - Zhou, Yan; Zhao, Zeqing; Zeng, Lulu; Peng, Jun; Zhou, Shuping; Min, Liang; Ke, Jiangwei; Liu, Jinhui
Abstract : Background. Carbapenem-resistant Klebsiella pneumoniae (CRKP) is increasingly isolated in paediatric wards, posing a severe threat to these vulnerable populations. This study investigated the clinical features, determinants of carbapenem resistance and clonal relatedness among CRKP in our hospital. Hypothesis. The prevalence of carbapenem-resistant K. pneumoniae in paediatric patients differs from the strains isolated from adult patients in carbapenemase and predominant clones. Aim. To investigate the pattern of carbapenemase and the clonal relationships between carbapenem-resistant Klebsiella pneumoniae in a paediatric hospital in Jiangxi Province. Methodology. Forty-five CRKP isolates were consecutively collected from October 2016 to October 2020. Medical records were reviewed to analyse clinical features. Detection of carbapenemase genes was used to determine CRKP resistance mechanisms and clonal relatedness among CRKP was identified through multi-locus sequence typing (MLST). Results. Forty-three (95.6 %) patients developed CRKP infection, and two (4.4 %) were colonized by CRKP in the urinary tract. The overall mortality rate was 13.3 %. In total, 42 (93.3 %) strains were positive for carbapenemase genes, and bla NDM (62.2 %) was the predominant gene. The MLST identified 24 different sequence types (STs) of CRKP, in which ST11 ( n =8, 17.8 %) and ST2735 ( n =8, 17.8 %) were the most common STs. Conclusion. The pattern of CRKP in paediatric patients reflects evolving changes. The ST2735 K. pneumoniae may present as a dangerous CRKP clone circulating in paediatric patients.